Proceedings of the 13th Annual ACM Symposium on User Interface Software and Technology - UIST '00 2000
DOI: 10.1145/354401.354435
|View full text |Cite
|
Sign up to set email alerts
|

Speed-dependent automatic zooming for browsing large documents

Abstract: We propose a navigation technique for browsing large documents that integrates rate-based scrolling with automatic zooming. The view automatically zooms out when the user scrolls rapidly so that the perceptual scrolling speed in screen space remains constant. As a result, the user can efficiently and smoothly navigate through a large document without becoming disoriented by extremely fast visual flow. By incorporating semantic zooming techniques, the user can smoothly access a global overview of the document d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
178
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(183 citation statements)
references
References 23 publications
0
178
0
Order By: Relevance
“…One last related zooming technique we have implemented is Igarashi and Hinckley's speed-dependent automatic zooming technique for large documents [6] [7]. This causes the view to smoothly zoom out while the user is scrolling a document rapidly.…”
Section: Zoomable Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…One last related zooming technique we have implemented is Igarashi and Hinckley's speed-dependent automatic zooming technique for large documents [6] [7]. This causes the view to smoothly zoom out while the user is scrolling a document rapidly.…”
Section: Zoomable Interfacesmentioning
confidence: 99%
“…As an additional navigational tool in our system, we have implemented speed-dependent scrolling [7]. This technique will automatically zoom out the view window when the user scrolls rapidly, which helps to ensure that the scrolling speeds appears more perceptually consistent to the viewer.…”
Section: System Overviewmentioning
confidence: 99%
“…1). This intuitive model for a navigator first was proposed and implemented by Igarashi and Hinckley [14] for browsing large documents and maps on Desktop PCs. Cockburn et al [1] suggested and successfully evaluated the refinements of this approach for navigating digital documents such as PDF files on Desktop PCs.…”
Section: Related Workmentioning
confidence: 99%
“…This paper reports a project that develops the Speed-Dependent Automatic Zooming method of navigation [14]. The SDAZ method applies to all digital navigation (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation